Tissue reaction surrounding miniscrews for orthodontic anchorage: An animal experiment - Stephanie Shih-Hsuan Chen; Hao-Hueng Chang; Yuan-Hou Chen; Yi-Ping Wang; Yunn-Jy Chen; Yi-Jane Chen; Hsiang-Hua Eddie Lai; Chung-Chen Jane Yao (Elsevier, 2012)
Background/purpose: Nowadays, mini-implant anchorage is incorporated for achieving a variety of orthodontic treatment goals. However, when a miniscrew is located in the interdental area, potential root contact may lead to miniscrew mobility or even failure. Therefore, miniscrew/root contact and possible tissue responses, including root repair, were histologically investigated in the current study. Materials and methods: Eight miniscrews were surgically placed in a single dog mandible. Among these, four miniscrews (experimental group) were intentionally placed in contact with a root and then retained for different time durations, three (control group) were also intentionally placed in contact with a root but were immediately removed after insertion, and one was placed without root contact and was retained for 24 weeks. The animal was sacrificed after 24 weeks. Results and conclusions: (1) Tissue surrounding roots damaged by a miniscrew showed a significant inflammatory response. (2) Root resorption was occasionally observed after 3 weeks following insertion of a miniscrew even if the miniscrew was not in direct contact with the root. (3) Root repair was noted with a cementoblast lining along the resorption surface at as early as 3 weeks after miniscrew insertion. Alveolar bone filled in the lesion when the root damage was large so that the contour of the alveolar bone followed that of the damaged root, with the width of the periodontal ligament space being maintained. (4) Stable miniscrews were mainly those which did not contact adjacent roots, and for which the surrounding tissue showed only a small inflammatory response with some extent of direct bone contact around the miniscrew. On the contrary, most of the failed miniscrews were those which had direct contact with adjacent roots, and which exhibited severe tissue inflammation and were covered by thick layers of soft tissue. Failure was detected 3 weeks after insertion. Surprisingly, the epithelial lining surrounding the miniscrews might not have spontaneously resolved 6 weeks after screw removal. Persistent infection in the sinus tract was noted, and this would require attention.